The β-carboline Harmine improves the therapeutic benefit of anti-PD1 in melanoma by increasing the MHC-I-dependent antigen presentation - Noman, Muhammad Zaeem; Bocci, Irene Adelaide; Karam, Manale; Moer, Kris Van; Bosseler, Manon; Kumar, Akinchan; Berchem, Guy; Auclair, Christian; Janji, Bassam (Frontiers in Immunology, 2022)
Harmine is a dual-specificity tyrosine-regulated kinase 1A (DYRK1A) inhibitor that displays a number of biological and pharmacological properties. Also referred to as ACB1801 molecule, we have previously reported that harmine increases the presentation of major histocompatibility complex (MHC)-I-dependent antigen on melanoma cells. Here, we show that ACB1801 upregulates the mRNA expression of several proteins of the MHC-I such as Transporter Associated with antigen Processing TAP1 and 2, Tapasin and Lmp2 (hereafter referred to as MHC-I signature) in melanoma cells. Treatment of mice bearing melanoma B16-F10 with ACB1801 inhibits the growth and weight of tumors and induces a profound modification of the tumor immune landscape. Strikingly, combining ACB1801 with anti-PD1 significantly improves its therapeutic benefit in B16-F10 melanoma-bearing mice. These results suggest that, by increasing the MHC-I, ACB1801 can be combined with anti-PD1/PD-L1 therapy to improve the survival benefit in cancer patients expressing displaying a defect in MHC-I expression. This is further supported by data showing that i) high expression levels of TAP1, Tapasin and Lmp2 was observed in melanoma patients that respond to anti-PD1; ii) the survival is significantly improved in melanoma patients who express high MHC-I signature relative to those expressing low MHC-I signature; and iii) high expression of MHC-I signature in melanoma patients was correlated with increased expression of CD8 and NK cell markers and overexpression of proinflammatory chemokines involved in the recruitment of CD8+ T cells.